Synthesis and properties of (−)-menthol-derived chiral liquid crystals by introducing adipoyloxy spacer between mesogenic core and chiral menthyl. Issue 10 (9th August 2018) - Zhu, Zhao-Xia; Luo, Cong-Cong; Wang, Ji-Wei; Hu, Jian-She; Jia, Ying-Gang
ABSTRACT: A homologous series of new chiral liquid crystal compounds, M6B n B ( n  = 2, 4, 6, 8, 10, 12, 14, 16, 18), with varying length of n -alkoxy chains at one end, was formed by covalently linking a chiral (− )-menthyl with biphenyl-benzoate via adipoyloxy spacer group. A combination of analysis methods such as Fourier transform infrared, 1 H NMR spectra, differential scanning calorimetry, polarised optical microscopy and X-ray diffraction was carried out to systematically investigate their phase structures and phase transition behaviours. The length of the flexible terminal alkoxy group has a profound influence on the clearing points ( T iso ) and T iso decrease with the increase of alkoxy chain ( n ). In addition, increasing the length of the terminal alkoxy group tends to narrow the temperature range of the N* phase and favour the development of chiral smectic C phase. Graphical Abstract: